How Did You Do It? Shared Experiences of Birth Activism on the Issue of Obstetric Violence: Interview with Ibone Olza - Skoko, Elena (Journal of the Motherhood Initiative for Research and Community Involvement, 2018)
Ibone Olza is a Spanish mother activist, psychiatrist, and author involved in childbirth advocacy and research at the national and international level. In the present interview, she talks about her experiences within Spanish mothers’ movement, specifically in relation to the phenomenon and the concept of “obstetric violence”—a form of gender-based violence exercised on women within maternity healthcare. The interviewer Elena Skoko is a fellow mother activist operating in Italy. The conversation herein represents a milestone for the Italian mothers’ movement because it has influenced the use of the term “obstetric violence” in Italy, which has resulted in the creation of a new public awareness and a new national movement of mothers.